1989
DOI: 10.1136/emj.6.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Beware the patient with a headache in the accident and emergency department.

Abstract: SUMMARYWe have reviewed the 130 patients presenting to an accident and emergency (A & E) department with a headache, followed up for 2 years. These are infrequent attenders but we have found that there is a high incidence of serious neurological pathology (16%) in this group of patients. We suggest that patients presenting to the A & E department with headache should be thoroughly examined and investigated and in the absence of a definite benign diagnosis should at least be admitted for a period of observation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
18
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 5 publications
8
18
0
Order By: Relevance
“…2,4,5 However, approximately 2% of all patients with headache and more than 18% of patients with sudden, severe headaches have a serious underlying cause. 4,[6][7][8][9] The frequency of secondary headaches also increases with age, occurring in almost 15% of headache sufferers older than 75 years. 4 The ED physician has the difficult task of discriminating between nonemergent headaches and those requiring acute care.…”
Section: Resultsmentioning
confidence: 99%
“…2,4,5 However, approximately 2% of all patients with headache and more than 18% of patients with sudden, severe headaches have a serious underlying cause. 4,[6][7][8][9] The frequency of secondary headaches also increases with age, occurring in almost 15% of headache sufferers older than 75 years. 4 The ED physician has the difficult task of discriminating between nonemergent headaches and those requiring acute care.…”
Section: Resultsmentioning
confidence: 99%
“…In all other reports, the most frequent ED diagnosis for primary headache was migraine [6, 1418]. In a nationwide study covering the period between 1992 and 2001 on headache management in US EDs, Goldstein et al [8] reported that the diagnosis of migraine was made in 63.5% of patients who attended the ED suffering from headache.…”
Section: Discussionmentioning
confidence: 99%
“…The authors comment on the low attendance rate of patients with this problem, but the high incidence of serious pathology detected. 2 If serious pathology is suspected or the diagnosis remains unclear, investigation may be indicated. Edmeads points out that investigation is necessary when the patient complains of the worst headache ever, onset of headache with exertion (more suggestive of SAH or raised intracranial pressure), reduced alertness or cognition, neck not perfectly supple (implying blood or pus in the cerebrospinal fluid (CSF)), any abnormality on examination (including fever), or worsening under observation.…”
mentioning
confidence: 99%